2016
DOI: 10.1161/strokeaha.115.011131
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Higher-Level Functional Capacity as a Predictor of Stroke in Community-Dwelling Older Adults

Abstract: S troke continues to be a major public health concern worldwide. As with other developed countries, it is the leading cause of death and a major neurological cause of long-term disability in Japan.1 Therefore, stroke prevention is a public health priority.Limitations in functional capacity after stroke are prevalent 2 because strokes often affect the memory and physical capabilities required to perform activities of daily living. A small but growing number of studies have challenged the conventional view that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…The aforementioned survival bias 6) may be more marked in diabetes mellitus than in other risk factors, although this remains to be proved. Previous studies have shown that functional capacity or psychosocial status, such as social role 19) , cognitive impairment 33) , and depression 34) , are significantly associated with stroke incidence even after adjusting for traditional risk factors among old-old adults. For those aged ≥ 75 years, these factors are likely to have stronger associations with stroke incidence than traditional risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned survival bias 6) may be more marked in diabetes mellitus than in other risk factors, although this remains to be proved. Previous studies have shown that functional capacity or psychosocial status, such as social role 19) , cognitive impairment 33) , and depression 34) , are significantly associated with stroke incidence even after adjusting for traditional risk factors among old-old adults. For those aged ≥ 75 years, these factors are likely to have stronger associations with stroke incidence than traditional risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The geographic and demographic characteristics of the study participants have been described previously 18, 19) . The total population aged ≥ 60 years was 2,614 in 1998; 2,348 provided written informed consent to participate (response rate 89.8%).…”
Section: Methodsmentioning
confidence: 99%
“…The geographic and demographic characteristics of the study participants have been described previously [12,13] . The institutional review board of Tohoku University School of Medicine and of Pharmaceutical Sciences and the Department of Health of the Ohasama Town Government approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…A decline in higher‐level functional capacity is known to be predictive of a decline in cognitive function or the occurrence of stroke . A decline in higher‐level functional capacity is an important clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…ADL includes basic activities of daily living, which are somewhat more complex instrumental ADL and higher‐level functional capacity that includes intellectual ability and social roles. A decline in higher‐level functional capacity is predictive of a decline in cognitive function or occurrence of cerebral stroke . A decline in higher‐level functional is thus a clinically important outcome.…”
Section: Introductionmentioning
confidence: 99%